Composite anti-aging organic silicon heat-conducting gasket and preparation method thereof
By using a composite process of polyethylene blend with silicone rubber and boron nitride whiskers in the thermally conductive material, a highly oriented thermal conductivity network is formed, and mechanical properties are enhanced by vulcanization treatment, the thermal management and high temperature stability of electronic components under high integration and high power are solved, and efficient thermal conductivity and anti-high temperature aging effects are achieved.
Patent Information
- Application Number
- CN202411797454.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-28
AI Technical Summary
In the process of high integration and high power development, modern electronic devices have caused electronic components to generate more heat in a limited volume. If they cannot be exported in time, it will affect the normal operation of integrated circuits and chips, and may even lead to burning. Existing thermally conductive materials have shortcomings in high temperature aging.
A composite anti-aging silicone thermal gasket is used, which is made of a polyethylene blend mixed with silicone rubber and boron nitride whiskers. Through ultrasonic treatment and repeated drafting processes, a highly oriented thermal conductivity network is formed; hydroxylated boron nitride whiskers are added to improve matrix stability and thermal conductivity, and mechanical properties are enhanced by vulcanization treatment.
It achieves efficient thermal conductivity and high-temperature aging resistance, enhances the mechanical properties of the gasket and the density of the thermal conductivity network, and effectively solves the problems of thermal management and high-temperature stability of electronic components.
Smart Images

Figure BDA0005177147030000071 
Figure BDA0005177147030000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive materials, in particular to a composite anti-aging organic silicon thermal conductive pad and a preparation method thereof. Background Art
[0002] The advent of the fifth generation of communication technology (5G) has brought with it the rapid development of the electronic technology industry. While modern electronic equipment is constantly developing towards high integration and high power, its size is tending to be smaller and lighter. In the field of electronic packaging, the miniaturization and miniaturization of the computer and electronics industries have brought new challenges to the application of electronic components in thermal management. Electronic packaging technology has become the main factor affecting the stability and reliability of electronic equipment. The goal of packaging is to improve the transmission speed, power and heat dissipation capacity, increase the number of input / output ports, reduce the size of devices, and reduce production costs while ensuring insulation reliability. Therefore, electronic packaging is developing in the direction of high integration, high density, high frequency, and high power chips. This development trend causes electronic devices to generate more heat in a limited volume. According to Moore's law of heat, the reliability of electronic components decreases by 10% for every 2°C increase in temperature. If the heat cannot be exported in time and accumulates too much, it will affect the normal operation of integrated circuits and chips, and in severe cases, it will burn electronic components. The rapid development of electronic packaging technology has continuously put forward new requirements for electronic packaging materials. Thermally conductive insulating polymers can be used as heat sinks to replace traditional materials. The thermally conductive particles filled in the polymer can not only improve the thermal conductivity of the polymer, but also reduce its thermal expansion coefficient, reduce the internal stress generated by the volume shrinkage of the packaging material during the curing process, and avoid problems such as internal lead disconnection. Summary of the invention
[0003] The purpose of the present invention is to provide a composite anti-aging organic silicon thermally conductive pad and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a composite anti-aging organic silicon thermally conductive gasket, which is prepared by mixing a polyethylene blend with silicone rubber and boron nitride whiskers.
[0005] Furthermore, a method for preparing a composite anti-aging organic silicon thermally conductive gasket comprises the following preparation steps:
[0006] (1) Pretreated silver particles and anhydrous ethanol are mixed, subjected to ultrasonic treatment at 21 kHz for 25 to 40 minutes, placed in ultra-high molecular weight polyethylene, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] is added and kneaded to obtain a polyethylene blend;
[0007] (2) The polyethylene blend, silicone rubber, and hydroxylated boron nitride whisker are mixed in a mass ratio of 1:1-2:0.01-0.03, and then kneaded and vulcanized to obtain a composite anti-aging silicone thermally conductive gasket.
[0008] Furthermore, the preparation method of the pretreated silver particles in step (1) is as follows: nanosilver and anhydrous ethanol are mixed in a mass ratio of 1:100, ultrasonicated at 21kHz for 5-15min, heated to 50-70°C, stirred at 60-130rpm for 100-150min, and then a 2wt% KH570-ethanol solution of 2-4 times the mass of the nanosilver is added dropwise at a rate of 0.1-0.6mL / s while ultrasonicating, stirred for 3-8h, centrifuged at 10000rpm for 5-10min, the precipitate is taken, washed with anhydrous ethanol for 3-6 times, and dried at 50-90°C for 5-8h.
[0009] Furthermore, the viscosity average molecular weight of the ultra-high molecular weight polyethylene in step (1) is 5.7×10 6 .
[0010] Furthermore, the mixing process parameters of step (1) are: temperature of 160-200° C., push-pull frequency of 0.5 Hz, and time of 5-30 min.
[0011] Furthermore, in step (1), the mass ratio of the pretreated silver particles, anhydrous ethanol, ultra-high molecular weight polyethylene, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is 0.07-0.12:3-6:50:0.15.
[0012] Furthermore, the preparation method of the hydroxylated boron nitride whisker in step (2) is as follows: boron nitride whisker and anhydrous ethanol are mixed in a mass ratio of 1 to 5:100, ultrasonicated at 21kHz for 10 to 40 minutes, a Tris-Buffer solution with a pH of 8.5 of 60 to 80 times the mass of the boron nitride whisker is added, stirred at 100rpm for 30 minutes, dopamine hydrochloride of 0.09 to 0.4 times the mass of the boron nitride whisker is added, and stirring is continued for 30 minutes, and then placed in a 60°C water bath, stirred for 5 to 10 hours, washed with deionized water for 3 to 6 times, and dried at 50 to 90°C for 5 to 8 hours.
[0013] Furthermore, the silicone rubber in step (2) is specifically Silicone elastomer.
[0014] Furthermore, the mixing process parameters of step (2) are as follows: temperature of 130-180° C., push-pull frequency of 0.5 Hz, and time of 30-80 min.
[0015] Furthermore, the process parameters of the vulcanization in step (2) are: pressure of 8-12 MPa, temperature of 180-220° C., and time of 10-30 min.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention utilizes ultra-high molecular weight polyethylene and nano-silver for physical blending, and during repeated stretching, the polyethylene gradually forms a highly oriented structure, wherein the molecular chains of the wafers are rapidly arranged and oriented along the stretching direction, and are connected in series to form microfibers, and the connecting molecular chains are regularly arranged axially and recrystallized to form a crystal bridge structure connecting the crystal blocks, at which time the silver particles are located between the crystal blocks, playing the role of bridging the crystals, forming a heat-conducting network with nodes for each other, and then mixed with silicone rubber as a skeleton structure, and hydroxylated boron nitride is added in the process Whiskers can prevent ultra-high molecular weight polyethylene from sliding, thereby improving the stability of the matrix and achieving high temperature aging resistance. After being stretched, boron nitride whiskers also form a highly ordered directional structure in the matrix, and then overlap each other to form a heat conduction path, and together with nanosilver, they also increase the density of the heat conduction network. Finally, after vulcanization treatment, the hydroxylated boron nitride whiskers and silicone rubber interact with each other to form hydrogen bonds, and at the same time, they can increase the physical cross-linking points between the rubber phase and each component, so that the cohesive energy of the matrix is evenly dispersed, thereby enhancing the mechanical properties of the matrix and improving the high temperature aging resistance of the gasket. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the composite anti-aging organic silicon thermal conductive pads prepared in the following examples are as follows:
[0019] Thermal conductivity: The thermal conductivity of the embodiment and the comparative example of the same size was measured by using a thermal conductivity meter in accordance with ASTM D 5470.
[0020] High temperature aging resistance: Take the embodiment and the comparative example of the same size and test their tensile strength according to GB / T528. After aging treatment, test their breaking strength again. The aging temperature is 150°C and the time is 80h.
[0021] Example 1
[0022] (1) Nanosilver and anhydrous ethanol were mixed in a mass ratio of 1:100, ultrasonicated at 21kHz for 5min, heated to 50°C, stirred at 60rpm for 100min, and then a 2wt% KH570-ethanol solution twice the mass of the nanosilver was added dropwise at a rate of 0.1mL / s while ultrasonicating, stirred for 3h, centrifuged at 10000rpm for 5min, the precipitate was taken, washed with anhydrous ethanol for 3 times, and dried at 50°C for 5h to obtain pretreated silver particles; the pretreated silver particles and anhydrous ethanol were mixed, ultrasonicated at 21kHz for 25min, and the viscosity average molecular weight was 5.7×10 6 The process parameters are as follows: temperature is 160°C, push-pull frequency is 0.5 Hz, and time is 5 min to obtain a polyethylene blend; the pretreated silver particles, anhydrous ethanol, and a viscosity-average molecular weight of 5.7×10 6 The mass ratio of ultra-high molecular weight polyethylene and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is 0.07:3:50:0.15;
[0023] (2) Boron nitride whiskers and anhydrous ethanol were mixed at a mass ratio of 1:100, ultrasonicated at 21kHz for 10 minutes, a Tris-Buffer solution with a pH of 8.5 of 60 times the mass of the boron nitride whiskers was added, stirred at 100rpm for 30 minutes, dopamine hydrochloride of 0.09 times the mass of the boron nitride whiskers was added, and stirring was continued for 30 minutes, and then placed in a 60°C water bath, stirred for 5 hours, washed with deionized water for 3 times, and dried at 50°C for 5 hours to obtain hydroxylated boron nitride whiskers; polyethylene blend, The silicone elastomer and hydroxylated boron nitride whisker are mixed in a mass ratio of 1:1:0.01, and then kneaded. The process parameters are as follows: temperature of 130°C, push-pull frequency of 0.5 Hz, and time of 30 min. Finally, a vulcanization treatment is performed. The process parameters are as follows: pressure of 8 MPa, temperature of 180°C, and time of 10 min, to obtain a composite anti-aging silicone thermal gasket.
[0024] Example 2
[0025] (1) Nanosilver and anhydrous ethanol were mixed at a mass ratio of 1:100, ultrasonicated at 21kHz for 10min, heated to 60°C, stirred at 90rpm for 130min, and then a 2wt% KH570-ethanol solution three times the mass of the nanosilver was added dropwise at a rate of 0.3mL / s while ultrasonicating, stirred for 5h, centrifuged at 10000rpm for 7min, the precipitate was taken, washed with anhydrous ethanol for 5 times, and dried at 70°C for 6.5h to obtain pretreated silver particles; the pretreated silver particles and anhydrous ethanol were mixed, ultrasonicated at 21kHz for 32min, and the viscosity average molecular weight was 5.7×10 6The ultra-high molecular weight polyethylene is prepared by adding pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] to the mixture, and mixing is performed. The process parameters are as follows: temperature is 180°C, push-pull frequency is 0.5 Hz, and time is 18 min to obtain a polyethylene blend; the pretreated silver particles, anhydrous ethanol, and a viscosity-average molecular weight of 5.7×10 6 The mass ratio of ultra-high molecular weight polyethylene and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is 0.1:4.5:50:0.15;
[0026] (2) Boron nitride whiskers and anhydrous ethanol were mixed in a mass ratio of 3:100, ultrasonicated at 21kHz for 25 minutes, a Tris-Buffer solution with a pH of 8.5 of 70 times the mass of the boron nitride whiskers was added, stirred at 100rpm for 30 minutes, dopamine hydrochloride of 0.2 times the mass of the boron nitride whiskers was added, and stirring was continued for 30 minutes, and then placed in a 60°C water bath, stirred for 8 hours, washed with deionized water for 5 times, and dried at 70°C for 6.5 hours to obtain hydroxylated boron nitride whiskers; polyethylene blend, The silicone elastomer and hydroxylated boron nitride whisker are mixed in a mass ratio of 1:1.5:0.02, and then kneaded. The process parameters are as follows: temperature of 150°C, push-pull frequency of 0.5 Hz, and time of 50 min. Finally, a vulcanization treatment is performed. The process parameters are as follows: pressure of 10 MPa, temperature of 200°C, and time of 20 min, to obtain a composite anti-aging silicone thermal conductive gasket.
[0027] Example 3
[0028] (1) Nanosilver and anhydrous ethanol were mixed in a mass ratio of 1:100, ultrasonicated at 21kHz for 15min, heated to 70°C, stirred at 130rpm for 150min, and then a 2wt% KH570-ethanol solution with a mass of 4 times that of the nanosilver was added dropwise at a rate of 0.6mL / s while ultrasonicating, stirred for 8h, centrifuged at 10000rpm for 10min, the precipitate was taken, washed with anhydrous ethanol for 6 times, and dried at 90°C for 8h to obtain pretreated silver particles; the pretreated silver particles and anhydrous ethanol were mixed, ultrasonicated at 21kHz for 40min, and the viscosity average molecular weight was 5.7×10 6 The process parameters are as follows: temperature is 200°C, push-pull frequency is 0.5 Hz, and time is 30 min to obtain a polyethylene blend; the pretreated silver particles, anhydrous ethanol, and a viscosity-average molecular weight of 5.7×10 6 The mass ratio of ultra-high molecular weight polyethylene and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is 0.12:6:50:0.15;
[0029] (2) Boron nitride whiskers and anhydrous ethanol were mixed at a mass ratio of 5:100, ultrasonicated at 21kHz for 40 minutes, a Tris-Buffer solution with a pH of 8.5 of 80 times the mass of the boron nitride whiskers was added, stirred at 100 rpm for 30 minutes, dopamine hydrochloride of 0.4 times the mass of the boron nitride whiskers was added, and stirring was continued for 30 minutes, and then placed in a 60°C water bath, stirred for 10 hours, washed with deionized water for 6 times, and dried at 90°C for 8 hours to obtain hydroxylated boron nitride whiskers; polyethylene blend, The silicone elastomer and hydroxylated boron nitride whisker are mixed in a mass ratio of 1:2:0.03, and then kneaded. The process parameters are as follows: temperature of 180°C, push-pull frequency of 0.5 Hz, and time of 80 min. Finally, a vulcanization treatment is performed. The process parameters are as follows: pressure of 12 MPa, temperature of 220°C, and time of 30 min, to obtain a composite anti-aging silicone thermal gasket.
[0030] Comparative Example 1
[0031] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: 6 Ultra-high molecular weight polyethylene and pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] were mixed, and the process parameters were as follows: temperature was 180°C, push-pull frequency was 0.5 Hz, and time was 18 min to obtain a polyethylene blend; the viscosity average molecular weight was 5.7×10 6 The mass ratio of ultra-high molecular weight polyethylene and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is 50:0.15; the remaining steps are the same as those in Example 2.
[0032] Comparative Example 2
[0033] The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: nanosilver and anhydrous ethanol are mixed in a mass ratio of 1:100, ultrasonicated at 21kHz for 10min, heated to 60°C, stirred at 90rpm for 130min, and then a 2wt% KH570-ethanol solution with a mass of 3 times that of the nanosilver is added dropwise at a rate of 0.3mL / s while ultrasonicating, and stirred for 5h, centrifuged at 10000rpm for 7min, the precipitate is taken, washed with anhydrous ethanol 5 times, and dried at 70°C for 6.5h to obtain pretreated silver particles; the pretreated silver particles and anhydrous ethanol are mixed, ultrasonicated at 21kHz for 32min, and the viscosity average molecular weight is 5.7×10 6The ultra-high molecular weight polyethylene was added with pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], the temperature was raised to 180°C, and the mixture was stirred at 100 rpm for 50 min to obtain a polyethylene blend; the pretreated silver particles, anhydrous ethanol, and a viscosity-average molecular weight of 5.7×10 6 The mass ratio of ultra-high molecular weight polyethylene and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] is 0.1:4.5:50:0.15; the remaining steps are the same as those in Example 2.
[0034] Comparative Example 3
[0035] The difference between Comparative Example 3 and Example 2 is that step (1) is omitted; the remaining steps are the same as those of Example 2.
[0036] Comparative Example 4
[0037] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: polyethylene blend, The silicone elastomers are mixed in a mass ratio of 1:1.5, and then kneaded. The process parameters are as follows: temperature of 150°C, push-pull frequency of 0.5Hz, and time of 50min. Finally, a vulcanization treatment is performed. The process parameters are as follows: pressure of 10MPa, temperature of 200°C, and time of 20min to obtain a composite anti-aging silicone thermally conductive gasket. The remaining steps are the same as in Example 2.
[0038] Comparative Example 5
[0039] The difference between Comparative Example 5 and Example 2 is that step (2) is different. Step (2) is changed to: boron nitride whiskers and anhydrous ethanol are mixed in a mass ratio of 3:100, ultrasonicated at 21kHz for 25min, a Tris-Buffer solution with a pH of 8.5 of 70 times the mass of the boron nitride whiskers is added, stirred at 100rpm for 30min, dopamine hydrochloride of 0.2 times the mass of the boron nitride whiskers is added and continued to be stirred for 30min, and then placed in a water bath at 60°C, stirred for 8h, washed with deionized water 5 times, and dried at 70°C for 6.5h to obtain hydroxylated boron nitride whiskers; the polyethylene blend, The silicone elastomer and hydroxylated boron nitride whisker were mixed in a mass ratio of 1:1.5:0.02, heated to 150°C, stirred at 100rpm for 50min, and finally vulcanized. The process parameters were as follows: pressure of 10MPa, temperature of 200°C, and time of 20min, to obtain a composite anti-aging silicone thermally conductive gasket. The remaining steps were the same as in Example 2.
[0040] Comparative Example 6
[0041] The difference between Comparative Example 6 and Example 2 is that step (2) is different. Step (2) is changed to: boron nitride whiskers and anhydrous ethanol are mixed in a mass ratio of 3:100, ultrasonicated at 21kHz for 25min, a Tris-Buffer solution with a pH of 8.5 of 70 times the mass of the boron nitride whiskers is added, stirred at 100rpm for 30min, dopamine hydrochloride of 0.2 times the mass of the boron nitride whiskers is added and continued to be stirred for 30min, and then placed in a water bath at 60°C, stirred for 8h, washed with deionized water 5 times, and dried at 70°C for 6.5h to obtain hydroxylated boron nitride whiskers; the polyethylene blend, The silicone elastomer and hydroxylated boron nitride whisker are mixed in a mass ratio of 1:1.5:0.02 and then kneaded. The process parameters are as follows: temperature of 150°C, push-pull frequency of 0.5 Hz, and time of 50 min. The mixture is placed in a mold and cured at room temperature to obtain a composite anti-aging silicone thermally conductive gasket. The remaining steps are the same as those in Example 2.
[0042] Effect example
[0043] Table 1 below shows the performance analysis results of the composite anti-aging organic silicon thermally conductive gaskets of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.
[0044] Table 1
[0045]
[0046]
[0047] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention utilizes ultra-high molecular weight polyethylene and nano-silver for physical blending. During the repeated drawing process, the polyethylene gradually forms a highly oriented structure, wherein the molecular chains of the wafer are connected in series to form microfibers, and then recrystallize to form a crystal bridge structure connecting the crystal blocks. At this time, the silver particles are between the crystal blocks, playing the role of bridging the crystals, forming a heat-conducting network that is mutually node-like. Then, it is mixed with silicone rubber as a skeleton structure, and hydroxylated boron nitride whiskers can prevent the ultra-high molecular weight polyethylene from sliding, thereby improving the stability of the matrix and achieving high temperature aging resistance. After being stretched, the boron nitride whiskers also form a highly ordered oriented structure in the matrix, and then overlap each other to form a heat-conducting path, and also increase the density of the heat-conducting network together with the nano-silver. Finally, after vulcanization treatment, the hydroxylated boron nitride whiskers and the silicone rubber interact with each other, and at the same time, the physical cross-linking points in the matrix can be increased, thereby enhancing the mechanical properties of the matrix and improving the high temperature aging resistance of the gasket.
[0048] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A composite anti-aging silicone thermally conductive pad, characterized in that: The composite anti-aging organic silicon thermally conductive pad is prepared by mixing a polyethylene blend with silicone rubber and boron nitride whiskers.
2. A method for preparing a composite anti-aging silicone thermally conductive pad, characterized in that: The method comprises the following preparation steps: (1) Pretreated silver particles and anhydrous ethanol are mixed, subjected to 21 kHz ultrasound for 25 to 40 minutes, placed in ultra-high molecular weight polyethylene, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] is added and kneaded to obtain a polyethylene blend; (2) The polyethylene blend, silicone rubber, and hydroxylated boron nitride whiskers are mixed in a mass ratio of 1:1-2:0.01-0.03, and then kneaded and vulcanized to obtain a composite anti-aging silicone thermally conductive gasket.
3. The method for preparing a composite anti-aging organic silicon thermally conductive gasket according to claim 2, characterized in that: The preparation method of the pretreated silver particles in step (1) is as follows: nanosilver and anhydrous ethanol are mixed in a mass ratio of 1:100, ultrasonicated at 21kHz for 5-15min, heated to 50-70°C, stirred at 60-130rpm for 100-150min, and then a 2wt% KH570-ethanol solution of 2-4 times the mass of the nanosilver is added dropwise at a rate of 0.1-0.6mL / s while ultrasonicating, stirred for 3-8h, centrifuged at 10000rpm for 5-10min, the precipitate is taken, washed with anhydrous ethanol for 3-6 times, and dried at 50-90°C for 5-8h.
4. The method for preparing a composite anti-aging organic silicon thermally conductive gasket according to claim 2, characterized in that: The viscosity average molecular weight of the ultra-high molecular weight polyethylene in step (1) is 5.7×10 6 .
5. The method for preparing a composite anti-aging organic silicon thermally conductive gasket according to claim 2, characterized in that: The mixing process parameters of step (1) are as follows: temperature of 160-200° C., push-pull frequency of 0.5 Hz, and time of 5-30 min.
6. The method for preparing a composite anti-aging organic silicon thermally conductive gasket according to claim 2, characterized in that: The mass ratio of the pretreated silver particles, anhydrous ethanol, ultra-high molecular weight polyethylene, and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] in step (1) is 0.07-0.12:3-6:50:0.
15.
7. The method for preparing a composite anti-aging organic silicon thermally conductive gasket according to claim 2, characterized in that: The preparation method of the hydroxylated boron nitride whisker in step (2) is as follows: boron nitride whisker and anhydrous ethanol are mixed in a mass ratio of 1 to 5:100, ultrasonicated at 21 kHz for 10 to 40 minutes, a Tris-Buffer solution with a pH of 8.5 in an amount of 60 to 80 times the mass of the boron nitride whisker is added, stirred at 100 rpm for 30 minutes, dopamine hydrochloride in an amount of 0.09 to 0.4 times the mass of the boron nitride whisker is added, and stirring is continued for 30 minutes, and then placed in a 60°C water bath, stirred for 5 to 10 hours, washed with deionized water for 3 to 6 times, and dried at 50 to 90°C for 5 to 8 hours to obtain the obtained product.
8. The method for preparing a composite anti-aging organic silicon thermally conductive gasket according to claim 2, characterized in that: The silicone rubber in step (2) is specifically SYLGARD 160® silicone elastomer.
9. The method for preparing a composite anti-aging organic silicon thermally conductive gasket according to claim 2, characterized in that: The mixing process parameters of step (2) are as follows: temperature of 130-180° C., push-pull frequency of 0.5 Hz, and time of 30-80 min.
10. The method for preparing a composite anti-aging organic silicon thermally conductive gasket according to claim 2, characterized in that: The process parameters of the vulcanization in step (2) are as follows: pressure of 8-12 MPa, temperature of 180-220° C., and time of 10-30 min.